Biodistribution and Absorption of Radiopharmaceutical 99mTc MDP in Various Bones of Lung Cancer Patients Using SPECT/CT Modalities (International Journal of Scientific Research in Science and Technology, 2024)
Lung-to-bone cancer metastasis frequently involves bone lesions, particularly in the vertebrae. A bone scan using the radiopharmaceutical 99mTc MDP is a common diagnostic tool for detecting advanced metastases. This research aimed to determine the conversion factor of count rate to unit activity, assess the range of source activity in bones with and without lesions, and analyze the relationship between lung cancer metastasis and radiopharmaceutical activity in various bones. The study involved 28 patients. Procedures included phantom manufacturing, determining the depth of Antero Posterior (AP) and Postero Anterior (PA) position bones, converting count rates to activity units, and assessing 99mTc MDP biodistribution in bones. Results indicated that the conversion factor of count rate to activity units in AP and PA positions for lumbar vertebrae, costa vera, ilium, and sacrum were (〖13.2×10〗^(-4); 4.9〖×10〗^(-4)) mCi/cps; (4.0〖×10〗^(-4); 4.4〖×10〗^(-4)) mCi/cps; (4.0〖×10〗^(-4); 4.9〖×10〗^(-4)) mCi/cps; and (〖12.2×10〗^(-4); 〖4.5×10〗^(-4)) mCi/cps. In addition, there is a range of source activity values and percentage of activity in the bones (lumbar vertebrae; costa vera; ilium; and sacrum), namely (0.019-0.053) mCi and (0.107-0.498)%; (0.020-0.045) mCi and (0.139-0.338)%; (0.024-0.066) mCi and (0.128-0.551)%; and (0.012-0.028) mCi and (0.078-0.264)%. Furthermore, there is a range of source activity values in the lesion-indicated bone (lumbar vertebrae; costa vera; ilium; and sacrum), namely (0.038-0.053) mCi; (0.024-0.045) mCi; (0.033-0.066) mCi; and (0.017-0.028) mCi. The relationship between lung cancer metastasis to various bones studied and the range of radiopharmaceutical activity values obtained is moderately positive.